Failure probability and stress distribution of milled porcelain-zirconia crowns with bioinspired/traditional design and graded interface. (July 2021) - Ramos, G.F.; Ramos, N.C.; Alves, L.M.M.; Kaizer, M.R.; Borges, A.L.S.; Campos, T.M.B.; Melo, R.M.
Abstract: Objective: To evaluate the failure probability and stress distribution of traditional and bioinspired porcelain-zirconia milled crowns, with and without silica infiltration (graded zirconia). Methods: Traditional crown design had a zirconia infrastructure veneered with porcelain; Bioinspired, had a porcelain infrastructure with translucent-zirconia veneer; Graded and Graded Bioinspired crowns had their zirconia layer infiltrated by silica (n = 25). The cameo surface of each crown (porcelain or zirconia) was glazed. The restoration layers were fused by a vitreous connector and the crowns were adhesively cemented to dies. The specimens were then mechanically cycled in a sliding machine using 100 N load at 4 Hz. The specimens were tested until 2 × 10 6 cycles, and every 0.5 × 10 6 cycles the crowns were evaluated under stereomicroscopy for the presence of failures. The stress distribution was inspected with Finite Element Analyses. Results: The predominant failure modes for the Traditional and Graded crowns were delamination and cracking, respectively. The Weibull parameters beta and eta were, respectively: Traditional 1.30 and 2.3 × 10 6 cycles, and Graded 1.95 and 2.3 × 10 6 cycles. Thus, the Traditional and Graded crowns presented greater susceptibility to failure due to fatigue, while the Bioinspired and Graded Bioinspired crowns showed no fatigue effect using 100N load, showing beta = 1 and eta of approximately 17 × 10 6 cycles. Also, through finite element analyses, it was verified that the Bioinspired and Graded Bioinspired crowns presented the best stress distribution on both crowns and dental structures. Significance: Bioinspired and Graded Bioinspired crowns had the lowest failure probability and better stress distribution and may be considered robust long lasting restorations. Highlights: Bioinspired crowns did not show fatigue-assisted damage after 2 million cycles. All bio-inspired crowns presented more favorable stress distribution. Graded crowns had reduced delamination failures compared to Traditional.